Adolescents’ advertising literacy and body self-perception in the face of influencer marketing - Beatriz Feijoo; Charo Sádaba (Cuadernos.info)
In today's society, people are increasingly conscious of their bodies, and marketers are well aware of this fact. As a result, influencers have started to include body-related content in their posts, especially when promoting fashion, food, cosmetics, beauty or fitness brands. This, and the influence that influencers' lifestyles have on users' body image, calls for a closer look at measures that can protect the public, especially young people, from the effects of these posts, which often blur the lines between organic and sponsored content. This study raises the possibility that one of these filters to protect this age group from sponsored content from influencers exploiting the image argument is their level of advertising literacy. Based on a survey applied to 1,055 adolescents aged 11 to 17 between April and June, 2022, living in Spain, a significant relationship was found between adolescents' concern about their body image and their level of advertising literacy in the face of these contents, especially in setting goals to achieve the perfect body and the importance of physical appearance in their self-perception. The gender, age and socioeconomic status of the respondents lead to nuances in the results. The discussion here is relevant for companies that include influencers in their marketing strategies, families, educators and public administrations.